To use or not to use artificial intelligence, that is the question: A study of artificial intelligence with strategic communication professionals in Portugal - Baptista, Raphaël; Belim, Célia (MedieKultur: Journal of media and communication research, 2024)
The adoption of Artificial Intelligence (AI) is rapidly increasing, reshaping both society and organizational landscapes. This transformative trend has inevitably reached strategic communication professionals, leading to various perceptions about its application in this field. This study explores these perceptions of uses and gratifications, perspectives on the influence of AI, as well as the practices of professionals operating in Portugal in the mentioned areas regarding the integration of AI into the exercise of their professions. The study employed a qualitative approach, using semi-structured interviews to collect data from communication professionals. The results from 21 interviews indicate a greater awareness of AI integration, especially after the launch of ChatGPT, and automated content generation as one of the biggest uses of AI. Although most respondents expressed favorable inclinations towards AI integration, some reservations persist related to replacing human expertise and creating dependency. The recommendations underline the imperative to train professionals to mitigate AI-related drawbacks, maintain a symbiotic relationship between AI and humans, and uphold ethical standards.